2007
DOI: 10.1177/1469787407077986
|View full text |Cite
|
Sign up to set email alerts
|

Integrating web-delivered problem-based learning scenarios to the curriculum

Abstract: This article reports on a small-scale research project (n=56) that investigated student educational gain. For the purposes of this study, gain is defined as an increase in the score that students obtain for pre/post intervention tests. Students received authentic exposure to the process via a web-delivered problem-based scenario. The students were randomly allocated to case and control groups. No statistically significant differences in educational gain were recorded between the two groups. However, the resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 10 publications
0
16
0
2
Order By: Relevance
“…A few recent studies showed that integrated approach of PBL pedagogy and online delivery model enhanced students' learning attitudes [11], better prepared students for applying the knowledge learned in the classroom [12], and provided a coherent and comprehensive learning environment [13,14]. These evidences support the presentation of real-world industrial problems using a virtual company framework.…”
Section: Scientific and Educational Feasibilitymentioning
confidence: 95%
“…A few recent studies showed that integrated approach of PBL pedagogy and online delivery model enhanced students' learning attitudes [11], better prepared students for applying the knowledge learned in the classroom [12], and provided a coherent and comprehensive learning environment [13,14]. These evidences support the presentation of real-world industrial problems using a virtual company framework.…”
Section: Scientific and Educational Feasibilitymentioning
confidence: 95%
“…Utilization of new media sources has made it possible to use the Internet as a communication source and natural education platform. 54,55 There are two intersecting dimensions of teaching. The first is passive/active dimension of student participation.…”
Section: Identifying Optimal Didactic and Teaching Methodsmentioning
confidence: 99%
“…63,64 The use of multimedia scenarios in problem-based learning has also been highlighted in the literature and has proven to be an excellent tool for curriculum development. 54,55,80 Students in problem-based learning are confronted with authentic concerns that demand their engagement in a process to solve a problem at hand. The learning process is an interactive group effort.…”
Section: Identifying Optimal Didactic and Teaching Methodsmentioning
confidence: 99%
“…Inside the classroom, case studies offer another practical solution to the tensions between vocational and academic learning, as they encourage a problembased learning (PBL) approach. Research has consistently shown that PBL can encourage active, independent and reflective learning; promote positive attitudes and greater engagement; and motivate kinaesthetic learners (Gossman et al 2007;Prince 2005). Biggs (2003) holds up PBL as an exemplar of aligned teaching because it focuses students all the way through the learning process on solving professional problems.…”
Section: Some Possible Solutionsmentioning
confidence: 99%